Creativity of Cengklungan Artists in Podho Rukun Temanggung Community - Puspita, Nisa Rahma; Utomo, Udi; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2020)
Cengklungan art is a native traditional art of Temanggung Regency which has several additional electrical components. This study aims to provide an overview of the creativity of Paguyuban Podho Rukun artists and the factors that influence their creativity. The study was conducted by using qualitative analysis research methods with the research location in Temanggung Regency. The instruments and data collection techniques used observation, interviews and document study. The data validity technique used data triangulation technique. Meanwhile, the data analysis and processing techniques were carried out by collecting, reducing, clarifying and verifying data. The creativity of the Cengklungan artist in Podho Rukun is the addition of several components to the curved instrument namely cables, spulls, tunning pegs, boards, and guitar strings. In addition, the Cengklungan artist also produced several songs with a pentatonic nuance. The work process of cengklungan artists has also been discussed from several 4P factors including person, process, press, and product.